TAX RATE AND NON-DEBT TAX SHIELD - Teja, Adrian (Economic Faculty, Attahiriyah Islamic University, 2019)
Firm can minimize their tax obligation by debt tax shield and non-debt tax shield (NDTS). However, research findings on how firm treat debt tax shield and NDTS, as a substitute or as a complement, remain inconclusive. This paper objective is to provide evidence on how firm usage of NDTSchange when tax rates change in Indonesia. Multivariate regression analysis performed with NDTSas dependent variable and tax rates change and debt level as independent variable. Multivariate regression analysis covering 73 Indonesia firms with 146 observations for the period of year 2008 to year 2010. Within this period, Indonesia corporate tax rate being reduce twice from 30% in 2008 to 28% in 2009 and 25% in 2010. This research find when tax rates is decrease, public firm increase their usage of NDTSwith a lag of one year and debt financing remain increased alongside with non-debt tax shield. This finding provide support to debt tax shield and NDTSas a complement.